2003
DOI: 10.1063/1.1561168
|View full text |Cite
|
Sign up to set email alerts
|

Local impedance imaging and spectroscopy of polycrystalline ZnO using contact atomic force microscopy

Abstract: A current detection scanning probe technique is developed that quantifies frequency-dependent local transport properties. The approach, referred to as nanoimpedance microscopy/spectroscopy (NIM), is based on impedance spectroscopy with a conductive atomic force microscopy (AFM) tip. NIM is applied to study the quality of a tip/surface contact and transport behavior of individual grains and grain boundaries in polycrystalline ZnO. Impedance spectra were measured in the frequency range 40 Hz to 110 MHz, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
97
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(98 citation statements)
references
References 9 publications
0
97
1
Order By: Relevance
“…Among them, we can cite nanoscale capacitance microscopy [1][2][3], electrostatic force microscopy (EFM) [4][5][6][7][8][9][10], nanoscale impedance microscopy [11,12], scanning polarization force microscopy [13][14][15][16], scanning microwave microscopy (SMM) [17,18] and nanoscale non-linear dielectric microscopy [19]. These techniques have allowed measuring the electric permittivity with nanoscale spatial resolution on planar samples, such as thin oxides, polymer films and supported biomembranes [2][3][4]8,10], and on non-planar ones, such as, single carbon nanotubes, nanowires, nanoparticles, viruses and bacterial cells [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we can cite nanoscale capacitance microscopy [1][2][3], electrostatic force microscopy (EFM) [4][5][6][7][8][9][10], nanoscale impedance microscopy [11,12], scanning polarization force microscopy [13][14][15][16], scanning microwave microscopy (SMM) [17,18] and nanoscale non-linear dielectric microscopy [19]. These techniques have allowed measuring the electric permittivity with nanoscale spatial resolution on planar samples, such as thin oxides, polymer films and supported biomembranes [2][3][4]8,10], and on non-planar ones, such as, single carbon nanotubes, nanowires, nanoparticles, viruses and bacterial cells [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…A number of authors 18,19,20 have demonstrated the use of an AFM as a probe for local electrochemical impedance spectroscopy.…”
Section: (D) Afm Based Impedance Measurementsmentioning
confidence: 99%
“…Before and after carrying out capacitance measurements, the system conductance was checked by measuring impedances of bare Au plates. 13 We first analyzed the dielectric properties of polymer nanoparticles as a function of AC frequency to study a circuit model of our system (Figure 3). Capacitances of polystyrene (PS) and polymethylmethacrylate (PMMA) particles in the diameter of 100 nm were also compared at 90 % of humidity as controls, and the capacitance of PMMA appeared higher than the PS capacitance as shown in Figure 4-(a), which is consistent with the order of their dielectric constants, 2.6 and 3.12, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Illustration of the probe configuration and its circuit model of the AC capacitance SPM. C virus is capacitance of virus, CPE is a constant-phase element, representing frequencydependent capacitance and resistance of AFM tip and air, 5,13 and R inst is resistance of the instrument. Capacitance spectra of (a) HSV1 (▼) and mutated HSV1 adding green fluorescence proteins in capsid (▽) (b) HSV2 (○) and envelope-extracted HSV2 (•).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation